Difference in attitude between college teachers and ski-school instructors by instruction for beginners skier - MIYOSHI Eiji; FUKUSHIMA Kunio; KIMURA Hiroto; HARADA Hitoshi (Journal of Ski Science, 2007)
The objectives of this research are to clarify the difference in instruction methods between carving ski and normal ski in the case of beginners' instruction, and to compare the difference in attitude regarding instruction methods between college teachers and ski-school instructors. The subjects were a total of 211 people, including physical education teachers of colleges and instructors of ski-schools.As the result of this survey, the following things became clear: 1) It was found that there is a difference in instruction methods between carving ski and normal ski instruction.In the case of carving ski instruction, carving techniques are introduced at early stages, while in the case of normal ski instruction, the technique of skidding is emphasized. On the other hand, the problems with the beginners' instruction, safety-considered content, the learning environment, and the selecting slope and lines did not vary according to the type of ski.2) Ski instructors tended more to modify the instruction methods according to the type of ski. In addition, it was found that ski instructors emphasize the viewpoint of the control of ski boards, while college teachers place emphasis on the viewpoint of the control of the skier's body.3) It was found that the purposes of college classes in skiing emphasize “ safety ”, “ manners, ” and “ contact with nature ” rather than skiing skills and physical strength . In addition, the study results state that college teachers focus on skiing skills and disregard physical strength compared with ski-school instructors